Magnetically enhanced gliding arc discharge for CO2 activation. Issue 35 (January 2020) - Li, Li; Zhang, Hao; Li, Xiaodong; Huang, Jingying; Kong, Xiangzhi; Xu, Ruiyang; Tu, Xin
Graphical abstract: Highlights: A novel magnetically enhanced gliding arc (MEGAD) is developed for CO2 activation. The arc motion behavior is optimized with the presence of a magnetic field. The plasma volume is significantly enlarged for chemical reactions in the MEGAD. The addition of magnet improves the CO2 conversion by 40.6% at flow rate = 1 L/min. Abstract: In this work, a novel magnetically enhanced gliding arc discharge (MEGAD) reactor was developed and investigated for the activation of carbon dioxide to produce value-added carbon monoxide. The effect of the external magnetic field on the gliding arc motion behavior, electrical characteristics and CO2 decomposition has been systematically investigated under different flow rates. Results indicate that the presence of the external magnetic field can remarkably enlarge the plasma region, due to the facilitating effect of Lorentz force, especially at a low flow rate. The gliding arc motions with and without a magnetic field at low flow rates show different patterns: a short-circuiting pattern of a "motionless" gliding arc without a magnetic field and a regular 'ignition – elongation – extinguishment' pattern of a motional gliding arc with a magnetic field. Interestingly, the MEGAD exhibits higher CO2 conversion in comparison to traditional gliding arc systems (up to 40.6% higher at flow rate = 1 L/min), especially at relatively low flow rates. The optimal CO2 dissociation performance achieved is: 12.2% CO2 conversion and 24.3% energy efficiency at 3000 mL/min or 11.2% CO2 conversion and 27.9% energy efficiency at 4000 mL/min, with the presence of magnetic field.